ASSOCIATION BETWEEN ADIPOSITY AND AGE IN ELDERLY WOMEN (Fiep Bulletin - online, 2015)
The human aging process is associated with a number of morphological and structural modifications. The increase on the amount and abdominal concentration of body fatness as a consequence of the aging is linked to many metabolic diseases, which can affect the elderly quality of life (KULLER et al., 1994). According to that, the utilization of body fatness indicators that can precisely detect the morphological alterations become indispensable in the clinical field. However, entities like the World Health Organization indicates the utilization of simple body fatness indicators, but with easy applicability and low operational cost  like the Body Mass Index (BMI) and Waist Circumference (WC) (WHO, 1998), as being also considered all-cause disease predictors (ACSM, 2003). The objective of the present study was (a) to investigate the changes on indicators of body fatness in older women with aging and (b) to analyze the relationship between BMI and WC cutoff points established by international institutions concerning its influence on risk factors. The anthropometric variables, body mass, height, body mass index, waist circumference and waist to hip ratio were obtained according to the procedures proposed by LOHMAN et al. (1988). The classification of risk factors for disease based in both BMI and WC following the classification proposed by the ACSM (2003). The results showed percentage alterations only for body mass 9.5% and height 2.3%, from the first age group to the last. The risk variability for disease in the normal classification was 17.1-28.8%; for the augmented classification was 27.738.8%, for high was 13.421.0%; for very high was 23.128.0% and for the extremely high classification was 0.0-3.1%. In conclusion, public health programs that can interfere with those morphological modification that occur in elderly women are advised
Keywords: .